Заметка о Pyrrhocoris apterus linn - Ярошевский, В. (Харьков : В Университетской типографии, 1870)
It is given the description and the characteristics of Hemiptera insects belonging to the family Lygaeidaæ in the article.
Keywords: Общество испытателей природы; Императорский Харьковский университет; насекомые полужесткокрылые; Hemiptera; Pyrrhocoris apterus linn; Lygaeidæ